Occurrence and distribution of rhabditis axei (rhabditida; rhabditidae) in African giant snails in southwestern Nigeria (2000)
African giant snails (Archachatina marginata ovum Pfeffer, 1858; A. marginata saturalis Philippi, 1849 and Achatina achatina Linne, 1758) were examined for the occurrence of Rhabditis axei Cobbold. 1884.Differences in parasite intensity between size groups of snails were highly significant (P < 0.05) for die 3 species compared. The mean egg and larval output per gram of faeces was higher in larger snails. The mean intensity of the nematode eggs excreted was higher (P < 0.05 ) than the mean of larval output for the 3 species of snails. The distribution of R. axei within the snail hosts revealed site preferences. They are mostly (88 %) located in the rectum of the snails.